English Student Teachers’ Academic Writing Strategies: A Survey Study - Nunung Fajaryani; Mukhlash Abrar; Riang Yulia Gilsih; Nelly Arif (Edukasi, 2021)
Student teachers need to have writing skills to support their academic activities and professional lives. Mastery of writing skills is interrelated to the use of academic writing strategies; metacognitive strategies, cognitive strategies and social strategies. The purpose of this study was to describe students' academic writing strategies, specifically in writing their thesis. This was a quantitative study with a survey design. The sample in this study involved 88 students. The instrument in this study was a questionnaire with a Likert scale. The results indicated that the most dominant strategy used by students was metacognitive. Furthermore, the results also showed that there were different strategies used by male students and female students. Male students preferred to use social strategies to cognitive strategies while female students like cognitive strategies rather than social strategies.